Enhancing Generation Z's Political Efficacy Through Social Media Political Influencers - Venus, Anter; Intyaswati, Drina; Ayuningtyas, Fitria; Lestari, Puji (Nyimak: Journal of Communication, 2025)
Previous research has shown that political influencers affect internal political efficacy. The widespread exposure of Generation Z to political influencers on social media raises the question of whether this exposure enhances political knowledge, comprehension, and skills. The study examines the linear impact of political influencers on internal political efficacy by categorizing exposure as low, medium, or high. A survey was distributed through social media platforms. The study population consisted of Generation Z social media users, selected through purposive sampling (N = 488). Eligibility criteria included being between the ages of 17 and 26, holding Indonesian citizenship, and following at least one political influencer on social media. Data were analyzed using linear regression with SPSS version 25. The findings indicate that the influence of political influencers varies according to the level of their following. Influencers significantly affected internal political efficacy only among participants who followed them moderately. This effect was seen only among individuals with low or average political interest. For those with a high interest in politics, the influence of political influencers was minimal, likely because these individuals seek information from other sources. These results contribute to understanding the non-linear relationship between political influencer exposure and internal political efficacy.Keywords: Generation Z, internal political efficacy, political influencers, political interest ABSTRAKStudi terdahulu telah menunjukkan adanya pengaruh dari political influencer terhadap internal political efficacy. Dengan begitu banyak terpaan political influencer yang dapat diterima Generasi Z melalui media sosial, memunculkan pertanyan apakah semua terpaan tersebut berfungsi optimal  dapat menambah pengetahuan, pemahaman, dan skill  di bidang politik dari Gen Z. Studi ini  bertujuan untuk mengevaluasi dampak linier dari political influencer terhadap internal political efficacy, dengan membaginya pada tiga kelompok tingkatan following (rendah, sedang, tinggi). Penelitian menggunakan metode survei yang dilakukan dengan mendistribusikan kuesioner melalui jejaring media sosial.  Populasi merupakan  Generasi Z pengguna media sosial, dan pengambilan sampel menggunakan teknik purposive sampling (N=488). Kriteria sampel adalah mereka dengan usia 17-26 tahun (Gen Z), warga negara Indonesia, dan mem follow minimum satu political influencer di media sosial. Analisis data menggunakan analisis regresi linier dengan  aplikasi SPSS 25. Hasil menunjukkan bahwa pengaruh influencer politik memiliki perbedaan pada tingkat following yang berbeda. Hanya pada kelompok following moderat, influencer memberikan dampak pada internal political efficacy Gen Z. Selain itu, pengaruh influencer hanya berlaku jika individu memiliki ketertarikan politik yang rendah atau rata-rata. Ketika individu memiliki ketertarikan politik yang tinggi maka pengaruh influencer cenderung berkurang, hal ini dimungkinkan karena mereka dengan ketertarikan politik yang tinggi cenderung akan mencari informasi dari sumber alternatif lainnya. Temuan ini memberikan sumbangan konseptual terkait adanya hubungan non linier dari pengaruh political influencer terhadap internal political efficacy. Kata Kunci: Generasi Z, efikasi politik internal, influencer politik, minat politik